Gestion Dynamique de la Nature Temporaire en Carrières - Seleck, Maxime; Boisson, Sylvain; Mahy, Grégory (Presses universitaires de Liège, 2022)
The guide is based on the experience gained during the LiFE in Quarries project. An EU LIFE Programme funded project. Running from 2015 to 2021, it demonstrated that operational biodiversity solutions can be proposed and implemented through controlled investments benefiting nature protection as well as the private sector. The general idea of the project was to define measures favorable to biodiversity acceptable to the private operator, legally and scientifically valid. The partnership forged on this basis included the private sector, regional authorities, scientists and NGOs. The project was led by FEDIEX (Fédération des Entreprises Extractives) in partnership with the Walloon region (Department of Nature and Forests), University of Liège - Gembloux Agro-Bio Tech - Biodiversity and Landscape Unit, Natagora asbl and the Scheldt Plain Nature Park.